2023
DOI: 10.1371/journal.pone.0289554
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically assisted internal fixation for treatment of acute ankle fracture: A systematic review and meta-analysis of comparative studies

Abstract: Background Arthroscopically assisted reduction and internal fixation (ARIF) allows for the assessment of joint congruity following anatomic reduction, identification of occult intra-articular lesions, and treatment of traumatic intra-articular pathologies. The aim of this systematic review and meta-analysis was to provide evidence on whether ARIF is an alternative treatment protocol for ankle fractures. Methods The PubMed, Embase, and Cochrane Library databases were searched independently by two investigator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The present study is to assess the functional outcome of different methods of managing diabetic ankle fractures. (5) demonstrates no statistically significant difference between studied groups as regard short form 36 score. Table (6) demonstrates that there is no statistically significant difference between studied groups as regard incidence of complications.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation

Comparison of Operative vs Non-operative Management of Ankle Fractures in Diabetic Patients: Prospective Randomized Trial

Mohammad Mohsen Said Ahmad Al-Batarny,
Prof. Ahmad Elsayed Magdy Mohammad Elhawary,
Prof . Yasser Mahmoud Roshdy Kandil
et al. 2023
J. Adv. Zool.
“…The present study is to assess the functional outcome of different methods of managing diabetic ankle fractures. (5) demonstrates no statistically significant difference between studied groups as regard short form 36 score. Table (6) demonstrates that there is no statistically significant difference between studied groups as regard incidence of complications.…”
Section: Resultsmentioning
confidence: 71%
“…Around 1% of ankle fractures patients progress to an end-stage ankle osteoarthritis after ORIF requiring another surgical intervention (arthroplasty or fusion). (2,3,4,5) Diabetes is considered a potential risk factor for complications in any fracture situation, but specially in any low extremity fracture, including ankle fracture. It was found that any diabetic ankle fracture is at a significantly higher risk of presenting any complication (approximately 2 times) independent to the method of treatment.…”
Section: Introductionmentioning
confidence: 99%

Comparison of Operative vs Non-operative Management of Ankle Fractures in Diabetic Patients: Prospective Randomized Trial

Mohammad Mohsen Said Ahmad Al-Batarny,
Prof. Ahmad Elsayed Magdy Mohammad Elhawary,
Prof . Yasser Mahmoud Roshdy Kandil
et al. 2023
J. Adv. Zool.